Cleft Palate Surgery: An Evaluation of Length of Stay, Complications, and Costs by Hospital Type. (July 2014) - Nguyen, Christine; Hernandez-Boussard, Tina; Davies, Sheryl M.; Bhattacharya, Jay; Khosla, Rohit K.; Curtin, Catherine M.
Objective: The purpose of this study was to assess length of stay (LOS), complication rates, costs, and charges of cleft palate repair by various hospital types. We hypothesized that pediatric hospitals would have shorter LOS, fewer complications, and lower costs and charges. Methods: Patients were identified by ICD-9-CM code for cleft palate repair (27.62) using databases from the Agency for Health Research and Quality Healthcare Cost and Utilization Project Kids' Inpatient Database from 1997, 2000, 2003, and 2006. Patient characteristics (age, race, gender, insurer, comorbidities) and facility resources (hospital beds, cleft palate surgery volume, nurse-to-bed ratio, pediatric intensive care unit [PICU], PICU intensivist, burn unit) were examined. Hospitals types included pediatric hospitals, general hospitals, and nonaccredited children's hospital. For each hospital type, mean LOS, extended LOS (LOS > 2), and complications were assessed. Results: A total of 14, 153 patients had cleft repair with a mean LOS of 2 days (SD, 0.04), mortality 0.01%, transfusion 0.3%, and complication <3%. Pediatric hospitals had fewer patients with extended hospital stays. Patients with an LOS >2 days were associated with fourfold higher complications. Comorbidities increased the relative rate of LOS >2 days by 90%. Pediatric hospitals had the highest comorbidities, yet 35% decreased the relative rate of LOS >2 days. Median total charges of $10, 835 increased to $15, 104 with LOS >2 days; median total costs of $4367 increased to $6148 with a LOS >2 days. Conclusion: Pediatric hospitals had higher comorbidities yet shorter LOS. Pediatric resources significantly decreased the relative rate of LOS >2 days. Median costs and charges increased by 41% with LOS >2 days. Further research is needed to understand additional aspects of pediatric hospitals associated with lower LOS.